Penerapan Manajemen Berbasis Sekolah dalam Mengembangkan Kualitas Peserta Didik - Suci Nurpratiwi; Amaliyah Amaliyah (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This study discusses school-based management in relation to developing the quality of students. The purpose of this study is to determine and analyze the steps of each component of school management that affect the quality development of students. To approach this problem, the theoretical references used by G.A. Cole regarding open system management, and also a theory about the concept Total Quality Management. The research method used in this research is a qualitative descriptive method with a case study approach. Data collection was obtained through observation, interview, and documentation techniques. This study concludes that the development of the quality of students can be supported through a good management process, the components that influence it include the instrumental input component, including the role of a good headmaster, competent educational resources and teaching staff, complete and supporting infrastructure facilities, components environmental input includes establishing good relations with the school environment, parents, and related institutions, the process component includes the management of a conducive learning process, and the implementation of school culture as a manifest of the hidden curriculum, the output component is enhancement the quality of students.